Synthesis of platinum nanoparticles on strontium titanate nanocuboids via surface organometallic grafting for the catalytic hydrogenolysis of plastic waste. Issue 3 (23rd December 2022) - McCullough, Katherine E.; Peczak, Ian L.; Kennedy, Robert M.; Wang, Yi-Yu; Lin, James; Wu, Xun; Paterson, Alexander L.; Perras, Frédéric A.; Hall, Jacklyn; Kropf, A. Jeremy; Hackler, Ryan A.; Shin, Youngho; et al.
Abstract : Pt/SrTiO3 nanoparticle catalysts have been synthesized by surface organometallic chemistry in solution on a 5 g scale. Pt/SrTiO3 selectively and repeatedly upcycles isotactic polypropylene into uniform liquid products with M n ∼ 200 Da. Abstract : Pt/SrTiO3 (Pt/STO), prepared on small scale by atomic layer deposition (ALD), is a capable heterogeneous catalyst for the selective hydrogenolysis of polyolefins to hydrocarbon oils, providing a promising approach for upcycling plastic waste. However, because deposition by ALD is costly and resource-intensive, a new synthesis of Pt/STO is needed to effectively scale catalyst production and pursue the commercialization of upcycling processes. To that effect, this work details a scalable deposition method for Pt/STO made by surface organometallic chemistry (SOMC) techniques using Pt(ii ) acetylacetonate or and trimethyl(methylcyclopentadienyl)platinum. The STO support was calcined (550 °C), treated with ozone (200 °C), and finally steamed (200 °C) to afford a clean STO surface populated with only hydroxyl groups. Pt precursors were dissolved in toluene and deposited onto STO. After reduction at 300 °C, the STO support was decorated with 1.0–1.5 nm Pt nanoparticles. The size and loading of these nanoparticles were varied by employing a multi-cycle deposition and oxidation and/or reduction process designed to ALD techniques. These Pt/STO catalysts hydrogenolyzed isotactic polypropylene into liquid products (>95% yield) with average molecular weights of 200–300 Da (∼25 carbon atoms) and narrow size distributions at 300 °C and 180 psi H2 .